2006
DOI: 10.1007/s00540-005-0356-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-type Ca2+ channel modulation on direct myocardial effects of diazepam and midazolam in adult rat ventricular myocytes

Abstract: Midazolam and diazepam have differential effects on cardiac E-C coupling. Diazepam, but not midazolam, enhances cardiac E-C coupling independent of L-type Ca2+ channel modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[8][9][10][11] Flumazenil inconsistently reverses this decrease. [8][9][10][11] Flumazenil inconsistently reverses this decrease.…”
Section: Discussionmentioning
confidence: 94%
“…[8][9][10][11] Flumazenil inconsistently reverses this decrease. [8][9][10][11] Flumazenil inconsistently reverses this decrease.…”
Section: Discussionmentioning
confidence: 94%
“…The findings reflect the increase in averaged force and thus, an index of energy consumption rate and pH i transients. In contrast, Ca 2+ channel blocker, verapamil, has negative inotropic effects on cardiac contractions ( Bell and McDermott, 1995 ; Kanaya et al., 2006 ). We further tested the effects of verapamil on cardiac contractions and pH i transients.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, several studies have shown that diazepam was able to affect cells by mechanisms related or unrelated to PBRs (24,26). For example, diazepam decreased the Ca 2+ transient and the L-type Ca 2+ channel, which are both important in the negative inotropism and chronotropism caused by this drug (27)(28)(29). In the same line, another study on guinea pigs' hearts indicated that the negative inotropic effect of diazepam referred to its calcium channel blocking effect (15).…”
Section: Discussionmentioning
confidence: 98%